Interleukin-6 deficiency influences cytokine expression in susceptible BALB mice infected with Leishmania major but does not alter the outcome of disease. - Titus, Richard G. (2001)
College of Veterinary Medicine & Biomedical Sciences. Colorado State University. Departments of Pathology and Environmental Health. Fort Collins, CO, USA